Catalog of cometary nebulae and related objects (−42◦ < δ < +60◦) - Parsamian, E. S.; Petrosyan, V. M.
The catalogue of cometary nebulae and related objects is compiled using the known up to the publication date lists.
Keywords: Astronomy